TREATMENT OF ACUTE PULPITIS IN PATIENTS WITH AIDS BY MEANS OF VITAL AMPUTATION (Academicia Globe: Inderscience Research, 2024)
Acute pulpitis presents unique challenges in patients with AIDS due to their compromised immune systems. Vital amputation, a minimally invasive procedure preserving the tooth's pulp vitality, emerges as a promising intervention. This article explores the advantages of vital amputation in AIDS patients, including reduced invasiveness, faster healing, and minimized systemic stress. Integration of antimicrobial therapy enhances treatment efficacy. Despite its potential, further research is needed to ascertain long-term efficacy and safety. Vital amputation offers a valuable alternative to traditional root canal therapy, addressing the complexities of acute pulpitis in AIDS patients while optimizing oral health outcomes.